An Analysis on Flouting Maxim in Hotel Transylvania - Anyelina, Missel; Firmawan, Hendro (JEdu: Journal of English Education, 2023)
Communication is one of important things in peoples daily lives. People tell, inform, and ask anything to their interlocutors by communicating. Conversation is one of activities that people do to communicate. Conversation can happen when there are at least two people to communicate in their familiar language. Movie can be the example media that not only shows usual conversational activity. In movies, participants occasionally disregard the Cooperative Principle. They may provide excessive or insufficient information, use ambiguous statements, make false claims, or bring up irrelevant points. This research focuses on the research aim to find out the types of flouting maxims used and the dominant flouting maxims used in the Hotel Transylvania. This research uses a descriptive qualitative method. In this study, the researcher applied Grice's theory to analyze data from the movie Hotel Transylvania. The data consisted of 40 instances where the maxim was flouted, as identified by the researcher using the theory. The result shows that there are 4 types of flouting maxims namely: flouting maxim of quantity (5 data), flouting maxim of quality (12 data), flouting maxim of relation (18 data), and flouting maxim of manner (5 data). Meanwhile the dominant flouting maxim used in the Hotel Transylvania movie is flouting maxim of relation (18 data).